1980
DOI: 10.1111/j.1460-2466.1980.tb01768.x
|View full text |Cite
|
Sign up to set email alerts
|

Images of Old Age in Television Drama Imported to Israel

Abstract: EMerly characters were numerous and rated positively on attributes of leadership, independence, and family functionality on imported TV programs shown in Israel.Hundreds of non-Western television stations broadcast the same programs imported from the U.S. and Europe (4). The characters portrayed on them, moreover, are drawn from one culture but may contribute to how people in other cultures perceive both Westerners and themselves. The process by which foreign media products are selected for importation has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The same pattern was found in the fourth study on older characters in television drama broadcast in Israel (Shinar et al, 1980). The authors found that two-thirds of the older characters were shown in rather high status jobs, such as senior employee, professional or executive positions, or owner of small independent businesses.…”
Section: Resultssupporting
confidence: 70%
“…The same pattern was found in the fourth study on older characters in television drama broadcast in Israel (Shinar et al, 1980). The authors found that two-thirds of the older characters were shown in rather high status jobs, such as senior employee, professional or executive positions, or owner of small independent businesses.…”
Section: Resultssupporting
confidence: 70%
“…Attributes were measured by using a 32-item scale of Rosencranz and McNevin's (1969) Aging Semantic Differential (ASD) scales, which were developed based on Osgood, Suci, & Tannenbaum's (1957) semantic differential scales. The Aging Semantic Differential (ASD) was developed to measure attitudes and quantify bias and negative stereotypes toward older people (Intrieri, von Eye, & Kelly, 1995;Rosencranz & McNevin, 1969;Shinar, Tomer, & Biber, 1980). Items have bipolar adjective pairs with seven response levels ranging from 1 to 7.…”
Section: Methodsmentioning
confidence: 99%
“…Many empirical studies have revealed underrepresentation of older people in the mass media. A content analysis of U.S. and European television dramas imported to Israel showed that people who are age 60 or older comprised 9.6% of the 562 characters analyzed (Shinar, Tomer, & Biber, 1980). This proportion was much less than that represented by other age groups, aged 50-59 (31.7%), 30-49 (38.4%), and 15-29 (20.3%).…”
Section: Underrepresenation Of Older People In the Advertisingmentioning
confidence: 99%
See 1 more Smart Citation